Divided ownership: Development and perspectives - Pavel Petr; Ondřej Horák; Petr Dostalík (DANUBE: Law, Economics and Social Issues Review, 2018)
Divided ownership gives rise to a number of problems. The reintroduction of the superficies solo cedit principle and the superficiary right of building into the Czech law does not, of course, mean the return of feudal relationships. However, it should be reminded that it disrupts indivisibility (exclusivity, completeness, limitlessness) of ownership, which is traditionally seen as the foundation of ownership right. The authors use primarily comparative and historical methods in their research on this topic. In its today form, we understand divided ownership as a simplification that serves as ideological abstraction for a situation where the owner is subject to a long-term limitation by a very broad in rem right of another, which is hereditary and alienable. In this context we talk about three approaches to divided ownership in jurisprudence: (a) it does not exist at all; (b) it is limited solely to the feudal era; (c) it is a general term without relation to any specific social situation.
Keywords: 330; Divided Ownership; Superficiary Right to Build; Roman Law; Ownership